Cost-effectiveness of cardiovascular risk classification based on Ankle-Brachial Index test in association to Framingham risk score. (25th November 2020) - Grasso, E; Maloberti, A; Cortesi, P.A; Micale, M; Mazzaglia, G; Occhi, L; Palazzini, M; Peretti, A; Cavasin, D; Pansera, F; De Chiara, B; Vallerio, P; et al.
Abstract: Objectives: An individual patient-data meta-analysis conducted on 24, 955 men and 23, 339 women showed that Ankle-Arm Index (ABI) in combination with FRS classifies female subjects with higher accuracy with no difference for male. The objective of this analysis is assessing the cost-effectiveness of ABI combine with FSR in primary prevention. Methods: A decisional analytical model was developed to simulate CV risk of asymptomatic female subjects, stratified in 3 CV risk categories. The model compares the primary prevention intervention (treatment of subjects at intermediate and high risk) based on the classification with FRS alone or in association with ABI<0.9 (FRS-ABI). The cost-effectiveness model used 10 years time-horizon and the point of view of the Italian National Health System. Results were presented as incremental cost-effectiveness ratios (ICERs) per QALY gained. Cost and outcomes were discounted at 3%. Results: FRS-ABI determined a reclassification to higher risks in 7% of the female population, with an increase in costs per patient (€3, 373 vs €3, 198) but also greater efficacy (8, 683 vs 8, 689 QALYs) over a 10 years time horizon, with an ICER of €47.065 per QALY gained. While using an ABI<1.10 cut-off we obtained an ICER of €28.688 per QALY gained over 10 years simulation. In the probabilistic sensitivity analysis, the FRS-ABI reported a 50% probability to be cost-effective with ABI<0.9 cut-off and 80% probability with ABI<1.1 at a willingness to pay threshold of €50, 000 per QALY. Conclusions: Our study showed that FRS and ABI combination is a potentially cost-effective CV risk classification approach in female population. Our results can help the healthcare decision makers in implementing better strategies for primary CV diseases prevention in Italy. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): ASST Niguarda Cà Granda Hospital, University of Milano-Bicocca, Milan, Italy